1980
DOI: 10.2527/jas1980.513577x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microbial Feed Additives on Performance of Starter and Growing-finishing Pigs

Abstract: SummaryThree trials were conducted to evaluate the effect of lactic acid-producing microbial feed additives (Probiotics) on performance of starting and growing-finishing pigs. Two commercially available probiotics, Probios (L. acidopbilus) and Feed-Mate 68 (Streptococcus faeciurn type Cernelle 68), were used. In the first of two starter trials, 192 crossbred pigs (initial weight 7 kg) were used in a 2 • 4 factorial arrangement of treatments, with Probios and antibiotics (ASP-250, lincomycin, tylosin) as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 10 publications
6
51
0
4
Order By: Relevance
“…Our findings concerning the immunopotantiation caused by probiotic administration concur with Pollmann et al, (1980); Zulkifli et al, (2000); Toms and Powvie (2001) ;Huang et al, (2004); Koenen et al, (2004). Also, Sevage et al, (1996) and Panda et al, (2000) demonstrated an increase in the serum immunoglobulins IgG and IgA after administration of competitive exclusion cultures.…”
Section: Results Listed In Tablesupporting
confidence: 75%
“…Our findings concerning the immunopotantiation caused by probiotic administration concur with Pollmann et al, (1980); Zulkifli et al, (2000); Toms and Powvie (2001) ;Huang et al, (2004); Koenen et al, (2004). Also, Sevage et al, (1996) and Panda et al, (2000) demonstrated an increase in the serum immunoglobulins IgG and IgA after administration of competitive exclusion cultures.…”
Section: Results Listed In Tablesupporting
confidence: 75%
“…Some studies reported that treatment of piglets with B. lactis increases blood leukocyte phagocytic and T-lymphocyte proliferative responses [75]. Similar results have been observed with gnotobiotic piglets, where feeding with L. acidophilus increases the white blood cells [61] and the antibody level [41].…”
Section: Immunomodulationsupporting
confidence: 73%
“…Many investigators reported that lactic acid bacteria have an important role in beneficial biological functions in industrial animals (Fuller, 1989;Gilliland and Speck, 1977;Juven et al, 1991;Pedigon et al, 1995;Tortuero, 1973). However, in spite of the positive effects of probiotics application in health care and improving feed conversion for industrial animals (Pollmann et al, 1980;Sissons, 1989), special probiotics for inland or sea fish have not yet been developed. At present, most fish farmers in Korea have used probiotics isolated from mammals to achieve growth promotion.…”
mentioning
confidence: 99%
“…DS-12 in the fish gut. Pollmann et al (1980) reported that the administration of Lactobacillus acidophilus induces a growth promotion effect in sibling and nearly matured pigs. Other researchers (Chateau et al, 1993;Fuller, 1989;Gilliland et al, 1980;Gorbach, 1990;Pedigon et al, 1995;Tortuero, 1973) also reported that the administration of lactobacilli improves intestinal microflora and promotes animal and human health.…”
mentioning
confidence: 99%